Reading practices in a male penitentiary: Access, repression and senses - Wemberson José de Souza; Maria Celeste Reis Fernandes de Souza (Arizona State University, 2019)
This article has as a matter of concern the defense of the right to education to the people in situation of imprisonment, and it proposes to discuss practices of reading of men, students of the Education of Young and Adult People, in a masculine penitentiary. As a theoretical and analytical reference, studies of the field of literacy and authors focusing on territory are mobilized. The research field is a state school that functions in the penitentiary, and the data were collected through observation of classes and interviews with 12  subjects. Different literacy events have been identified in which men participate, but there is a tension between increasing access to reading and the limitations of the prison. These events constitute literacy practices in which multiple meanings appear, in addition to the possibility of remission of the sentence through reading, and the school is configured in prison as an important literacy agency, increasing the access to reading of these subjects and other men arrested and who do not attend classes. The results point to the need to strengthen the right to education in prisons, effectively guaranteeing access to school and to reading for people deprived of their liberty.